Human simulation for task-based survivability analysis. (2016) - Marler, Timothy; Capdevila, Nic; Kersten, Jake; Taylor, Andrew; Wagner, Samantha; Mackiewicz, Jim
Personal protective equipment (PPE) is increasingly approached from a systems perspective, and one must consequently consider human systems integration (HSI). However, tools for virtual analysis in this regard are lacking. Few human models have the ability to design or import complex PPE systems and then test them from an HSI perspective. Thus, we propose capabilities that allow for improved balance between mobility and coverage, and thus improved survivability. We contend that the propensity for survivability depends critically on the task being completed and on anthropometry. We present a suite of integrated tools for simulating: 1) war fighter interaction with body armour; 2) mission-critical tasks; 3) internal viscera that scale and move appropriately; 4) ballistic threats with statistical analysis. We have also developed methods for displaying external results within a human modelling framework, for inter-process communication, and for using external data as objective functions with optimal design of PPE-human systems.